Use of fabrics and bodies of adult plants of coniferous breeds for in vitro manifolding. (Experimental biology, 2015)
In our work attempts to study ability to manifolding of fabrics of adult plants of a pine ordinary were made and atewith ordinary in vitro depending on age of primary eksplant and conditions of his cultivation.
Keywords: microclonal manifolding; morphogenesis; coniferous plants; pine ordinary (Pinus sylvestris L.); fir-tree ordinary (Picea abies L.)